RESEARCH-BASED LEARNING: EFFECTS ON THE METACOGNITIVE AWARENESS OF SENIOR HIGH SCHOOL STUDENTS - Mark Anthony Catedral Mamon; Alejandro Galban Esperanza; Julie Anne Tapit Vital (IJIET (International Journal of Indonesian Education and Teaching), 2020)
This research study assessed the effects of research-based learning (RBL) on the metacognitive awareness of senior high school (SHS) students, specifically metacognitive knowledge and metacognitive regulation, and the correlation between their subcomponents. Fifty-six (56) Grade 12 students who have taken research subjects were obtained as respondents using purposive sampling. The respondents answered a 52-item metacognitive awareness inventory (MAI) with 17 items on metacognitive knowledge and 35 items on metacognitive regulation. Findings show that RBL developed a high level of conditional, procedural, and declarative knowledge among SHS students. The learning approach also developed a very high level of debugging strategies, and a high level of planning, information management system, evaluation, and comprehension monitoring. Furthermore, there is a weak or a moderately significant positive correlation between some subcomponents of metacognitive knowledge and metacognitive regulation as the effect of RBL. In conclusion, RBL has a considerable impact on the metacognitive awareness subcomponents of Grade 12 students.